New data on the genus Hybos Meigen (Diptera: Hybotidae) from the Palaearctic Region - Shamshev, Igor; Grootaert, Patrick; Kustov, Semen (Zootaxa, 2015)
The taxonomy and distribution of the genus Hybos Meigen in the Palaearctic Region is reviewed with a special reference to the European fauna. Twenty-three species have been recorded from the Palaearctic, of which only four species are known from Europe. We describe two new species, H. andradei sp. nov. (Portugal) and H. mediasiaticus sp. nov. (Middle Asia). The status of two previously considered doubtful species of Hybos are validated: H. striatellus Villeneuve, 1913 (Algeria) and H. vagans Loew, 1874 (the Caucasus). Both species are re-described, and the lectotype of H. striatellus is designated. A key to species of Hybos from the western Palaearctic is compiled. Numerous new data on distributions of H. culiciformis (Fabricius, 1775), H. femoratus (Müller, 1776), H. grossipes (Linné, 1767) and H. vagans are given. Hybos culiciformis is recorded for the first time from Algeria, Byelorussia, Croatia, Cyprus, Lebanon, and Portugal; H. femoratus—from Estonia, Georgia (including Abkhazia), Kazakhstan, Mongolia and Ukraine; H. grossipes—from Byelorussia, Estonia, Kazakhstan, Latvia, Mongolia, Ukraine; H. vagans—from Armenia, Azerbaijan, Georgia (including Abkhazia), Russia, Turkey. The variation of some characters in H. culiciformis is discussed and is confirmed for Portugese specimens by COI barcoding. Female postabdominal structures are examined and described for H. andradei sp. nov., H. culiciformis, H. femoratus, H. grossipes, H. mediasiaticus sp. nov., and H. striatellus. Possible relationships of the West-Palaearctic species are discussed. A check-list of Hybos from the Palaearctic Realm is provided.